Facile fabrication of a three-dimensional gold nanowire array for high-performance electrochemical sensing - Shi, L.; Chu, Z.; Liu, Yu; Jin, W. (R S C Publications, 2015)
Great challenges remain in the template-assisted fabrication of metal nanowire arrays on substrates, because enormous effort is required to address the adhesion issues between substrates and adopted templates, e.g. anodic aluminum oxide (AAO). Therefore, novel and promising templates are highly desired for the construction of proposed structures. Here, vertical 1,5-diaminoanthraquinone (DAAQ) nanowires were prepared in situ on substrates by a facile method, and these were proven to be a reliable and alternative template for the preparation of a metal nanowire array. As an example, with the wet chemical reduction of HAuCl4, a three-dimensional gold nanowire array (3D GNA) was successfully obtained with a DAAQ template. The proposed 3D GNA has an extremely large roughness factor of ca. 15, as well as high stability and a favorable surface structure for the diffusion of analytes, making it a suitable candidate for the construction of high-performance electrochemical biosensors. As a result, an ultrasensitive aptasensor was constructed for the detection of thrombin, with a general sensing scheme. The fabricated aptasensor displays an impressively ultralow detection limit of 3 fM (S/N = 3) with a wide linear response from 10 fM to 1 nM, as well as excellent selectivity, good reproducibility and acceptable stability. Further, the biosensor exhibits potential for application in the analysis of real serum samples. The developed DAAQ nanowires are envisaged to become a general template for the fabrication of more nanowire arrays and the as-synthesized 3D GNA could open up a wide range of possibilities for potential applications in biological sensing.